Toughness by segmentation: Fabrication, testing and micromechanics of architectured ceramic panels for impact applications. (February 2019) - Mirkhalaf, Mohammad; Sunesara, Amanul; Ashrafi, Behnam; Barthelat, Francois
Abstract: Precise material architectures and interfaces can generate unusual and attractive combinations of mechanisms and properties. For example, the segmentation into blocks of finite size and well-defined geometries can turn brittle ceramics into tough, deformable and impact resistant material systems. This strategy, while scarcely used in engineering, has been successfully used for millions of years in biological materials such as bone, nacre or tooth enamel. In this work, the precise relationships between architecture, mechanics, and properties in architectured ceramic panels are explored using a combination of mechanical testing with stereo-imaging, 3D reconstruction, and finite-element/analytical modeling. In particular, this work shows that a fine balance of interlocking and block size generates controlled frictional sliding and rotation of blocks, minimizes damage to individual blocks and optimizes performance. These ceramic architectured panels have 1/4 to 1/2 of the strength of monolithic ceramic panels, but they can absorb 5 to 20 times more mechanical energy, making them very attractive for applications where high surface hardness or high resistance to temperature must be combined with resistance to impact and toughness. Graphicalabstract :